An interactive serious game for dementia prevention - Yew, Wei Hong (2022)

(untitled)
In the recent years, the situation of rapidly aging population growth in most parts of the world creates a worrying situation. There is also a rise in age-related diseases associated with cognitive deficits, such as dementia. Normal cognitive status plays an essential role in controlling individuals' thinking and action to carry out normal daily activities. A healthy cognitive status could lower the risk of an individuals in getting cognitive impairments. A serious game related with game development. The serious game is a game with other purposes besides entertainment such as education, healthcare, and training. The main motivation of the project is to develop a serious game that could assess and train the potential risk factors that lead to cognitive impairments such as dementia. The serious game for dementia prevention can prevent or slow down the cognitive decline in an individual. The project aims to develop a serious game application for dementia prevention, create awareness among the public about dementia, and provide a cost-free serious game that could be played by elderly to prevent dementia. The contribution of this project will be creating a Malaysia-themed serious game for dementia prevention which is cost-free and available for anyone who is interested. The serious game will train and assess the cognitive functionalities related to dementia using test based on Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA). The project is expected to help in lowering the growth of dementia and increase the awareness among the public about dementia using a cost-free serious game for dementia prevention.